Digital Leadership Kepala Sekolah Hubungannya dengan Kinerja Guru dan Kompetensi Siswa Era Abad 21 - Agus Timan; Mustiningsih Mustiningsih; Ali Imron (Universitas Negeri Malang, 2022)
Abstract: The purpose of this study was to identify the relationship between five principal digital leadership constructs, namely visionary leadership, digital age learning culture, excellence in professional practice, systemic improvement, and digital citizenship with teacher performance and student competence in the 21st century. The number of samples in This study consisted of 96 people consisting of principals and teachers from 24 schools. The data analysis in this study used SEM with the help of the AMOS 24 program. The results showed that the five components of digital leadership namely visionary leadership, digital age learning, excellent in professional, systemic improvement, and digital citizenship have a direct effect on teacher performance and student competence in the century era. 21. The five components of digital leadership also indirectly affect student competence through teacher performance. The contribution of this research shows that with adequate digital leadership practices, supporting the efforts of teachers in achieving the expected performance, can improve student competence in the 21st century era.Keywords: digital leadership, teacher performance, student competence, elementary school Abstrak: Tujuan penelitian ini adalah untuk mengidentifikasi hubungan antara lima konstruksi kepemimpinan digital kepala sekolah, yaitu kepemimpinan visioner, budaya pembelajaran zaman digital, keunggulan dalam praktik profesional, peningkatan sistemik, dan kewarganegaraan digital dengan kinerja guru dan kompetensi siswa di abad 21. Jumlah sampel dalam penelitian ini sebanyak 96 orang terdiri dari Kepala Sekolah dan Guru dari 24 Sekolah. Analisis data dalam penelitian ini menggunakan SEM dengan bantuan program AMOS 24. Hasil penelitian menunjukkan kelima komponen digital leadership yakni visionary leadership, digital age learning, excellent in professional, systemic improvement, dan digital citizenship berpengaruh secara langsung terhadap kinerja guru dan kompetensi siswa di era abad 21. Kelima komponen digital leadership tersebut juga berpengaruh secara tidak langsung terhadap kompetensi siswa melalui kinerja guru. Kontribusi penelitian ini menunjukkan bahwa dengan praktik kepemimpinan digital yang memadai, mendukung upaya guru dalam mencapai kinerja yang diharapkan, dapat meningkatkan kompetensi siswa diera abad 21.Kata kunci: digital leadership, kinerja guru, kompetensi siswa, sekolah dasar